Politik Uang dalam Pemilihan Kepala Daerah terhadap Konstruksi Pemerintahan di Desa Bohar Sidoarjo - Suyono; I Wayan Arsana (Medan Resource Center, 2022)
The general election for regional heads or the 2020 Sidoarjo post-conflict local election should be an important stage in social and state life, because in this post-conflict local election, the community is involved or is involved as a fundamental element that determines the functioning of democracy. Democracy will maintain its sanctity in the hands of post-conflict local election organizers and the people. One of the political crimes and legal deviations that tarnishes the image of a democratic party is money politics. This study aims to analyze the practice of money politics carried out by political elites with the aim of buying people's votes and forms of politicians'behavior that damage government buildings. The research method used is qualitative research equipped with an analytical, conceptual approach, prioritizing primary data and secondary data with qualitative analysis. The results of the study show that the causes of the practice of money politics carried out by political elites with the aim of buying people's votes include: money is the root of problems and damage to government and democracy buildings, and the power of bribery practices has entered the deepest pores or networks of people's lives. , both to fight for and reap the values and norms of goodness, justice, and human dignity.